AB0640 Has Kawasaki Disease Lost its Articular Manifestations?. (9th June 2015) - Alvarez Andrés, E.P.; Rey, F.; Peña, C.; Collado, P.; Rubio, A.; Crespo, M.; Calvo, C.
Abstract : Background: Kawasaki Disease is a systemic vasculitis with an acute onset that affects primarily children under 5 years old. Even though its etiology is unknown, it can be preceded with viral infections. Its diagnosis is mainly clinical and its prognosis depends on cardiac complications. Acute arthritis was a very common finding in the pre-inmunoglobulins era. Nowadays with Inmunoglobulins treatment, it's hard to find studies that mention articular manifestations. Objectives: Our objective is to define arthritis prevalence in Kawasaki Disease at the time of diagnosis and its evolution. Methods: It is a retrospective analysis of 42 patients with Kwasaki Disease, diagnosed between January 1988 and November 2013. Demographic, clinical, laboratory and treatment variables were analysed. The clinical evolution was analysed with a statistic program (SPSS.V.10). Results: It was described a previous infection in 33, 3%. Male children were predominant (57, 1%), presenting diagnostic criteria: fever (100%), rash (92, 9%), conjunctival inyection (78, 6%), erythema of oral cavity (76, 2%), swollen lymph node in the neck (71, 4%), swelling and peeling in arms and legs (52, 4 and 46, 3% respectively). 8 patients had an altered echocardiogram (ectasy 14, 3% and aneurism 4, 8%). 50% of altered echocardiogram belonged to Incomplete Kawasaki. Seven patients (16%) presented arthritis at the onset (10 first days), mainly oligoarticular (57%), less than 4 joints, most of them ankles. We observed also, monoarticular arthritis (hip) in 2 patients (29%) and polyarticular in 1 patient (14%). Arthritis did not respond to Dalsy at first, but it responded to Inmunoglobulins IV, with ulterior effects. None of them had heart affectation. They have also a poor relationship with incomplete kawasaki. When admitted at the hospital: 14, 3% had leukocytosis, 2, 4% low platelets count, 42, 9% hypoalbuminemia and 14, 3% had an abnormal urianalysis. When talking about acute phase reactants: 92, 9% presented an elevated CRP (88.1±58; [38-125]) and 78, 6% and elevated ESR (69±30; [47.7- 92]). 71, 4% of the patients were monitored afterwards, and 81% did not have any complications, non cardiac or articular. Conclusions: Acute arthritis was unusual (16%), and with no ulterior complications. Cardiac affectation prevailed in incomplete kawasaki. Treatment with Inmunoglobulins IV and aspirin most likely prevents arthritis manifestations in Kawasaki Disease, therefore reducing monitorization with us. References: Gong GW, et al. Arthritis presenting during the acute phase of Kawasaki disease. J Pediatr 2006:148:800-5 Disclosure of Interest: None declared